2013
DOI: 10.1055/s-0033-1345150
|View full text |Cite
|
Sign up to set email alerts
|

High-fat Diets Containing Soybean or Canola Oil Affect Differently Pancreas Function of Young Male Rats

Abstract: The excessive fat intake generally might induce obesity and metabolic disturbances. Thus, the goal of the study was to assess the role of high-fat diets containing soybean or canola oil on intra-abdominal adiposity and pancreatic morphology and function of young rats. After weaning, rats were fed with a control diet (7S) or a high-fat diet containing soybean oil (19S) or canola oil (19C) until they were 60 days old, when they were sacrificed. Food intake (g/day), body mass and length, retroperitoneal and epidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In the figure 25 , the 19C (19% canola oil) group showed higher insulin resistance (HOMA-IR) and more damage to pancreas β-cells than the 19S (19% soybean oil) and 7S (control) groups. The 19C group presented lower percentage of pancreatic islets area in comparison to 19S (-41%) and 7S group (-70%, p < 0.0001) [51] . DM patients in Japan are characterized by exhibiting both insulin resistance and impaired insulin secretion.…”
Section: Link Between the Survival-shortening Activity Of Fats And Oimentioning
confidence: 74%
See 1 more Smart Citation
“…In the figure 25 , the 19C (19% canola oil) group showed higher insulin resistance (HOMA-IR) and more damage to pancreas β-cells than the 19S (19% soybean oil) and 7S (control) groups. The 19C group presented lower percentage of pancreatic islets area in comparison to 19S (-41%) and 7S group (-70%, p < 0.0001) [51] . DM patients in Japan are characterized by exhibiting both insulin resistance and impaired insulin secretion.…”
Section: Link Between the Survival-shortening Activity Of Fats And Oimentioning
confidence: 74%
“…Similarly, these 2 vegetable oils differentially affected oxidative stress-related enzymes in erythrocytes and vascular properties in the SHRSP rat [52] . da Costa et al [51] ascribed the difference in these parameters observed between the canola and soybean oil groups to the difference in the proportion of monounsaturated oleic acid and polyunsaturated linoleic acid ( fig. 25 ).…”
Section: Link Between the Survival-shortening Activity Of Fats And Oimentioning
confidence: 99%
“…As an example, MUFA‐rich macadamia oil (80% w/w) increased whole body adiposity in high‐carbohydrate, high‐fat diet‐induced model of metabolic syndrome . Similarly, high‐fat diet containing oleic acid‐rich canola oil increased abdominal fat in young rats . Pig lard and beef tallow, usually containing 40–50% oleic acid, both increase adiposity in rats and mice and are commonly used animal models of diet‐induced obesity .…”
Section: Fatty Acids: Saturated N‐9 N‐6 and N‐3 Fatty Acidsmentioning
confidence: 99%
“…Some studies have analyzed the effects of SO on obesity and diabetes; however, the results have been divergent. [ 14–16 ] Although these guidelines are still in force today, [ 3 ] recent literature has discussed about which type of fat would be the most harmful to health. [ 17 ] Studies indicate that saturated fat from sources such as CO, which in turn is rich in MCFAs, can play a beneficial role in both the prevention and treatment of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%